2016
DOI: 10.2196/medinform.4756
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Secure Sharing of Personal Health Data in the Cloud

Abstract: BackgroundInternet-based applications are providing new ways of promoting health and reducing the cost of care. Although data can be kept encrypted in servers, the user does not have the ability to decide whom the data are shared with. Technically this is linked to the problem of who owns the data encryption keys required to decrypt the data. Currently, cloud service providers, rather than users, have full rights to the key. In practical terms this makes the users lose full control over their data. Trust and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The most mentioned is a possible lack of data protection and violation of privacy. Nowadays, it is possible to encrypt data and transfer it via a highly secure line to a server or cloud [23,24]. Further, the right of medical confidentiality and the right to informational self-determination are not violated by the use of telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…The most mentioned is a possible lack of data protection and violation of privacy. Nowadays, it is possible to encrypt data and transfer it via a highly secure line to a server or cloud [23,24]. Further, the right of medical confidentiality and the right to informational self-determination are not violated by the use of telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Data transfer to a cloud or server needs to be encrypted to ensure the best possible protection of highly sensitive patient information. He et al ( 22 ) showed that few Android mHealth apps match these criteria, although technical capabilities are already established: Thilakanathan et al ( 23 ) developed a secure protocol for sharing patient data in clouds, and Silva et al ( 24 ) presented the DE4MHA algorithm for secure encryption. Moreover, data storage needs to be encrypted to protect patient data from unauthorized access.…”
Section: Limitations and Barriers Of Smartrctsmentioning
confidence: 99%
“…A line of research has been devoted to encryption-based secure data exchange. Thilakanathan et al (64) proposed a secure protocol for users to control the encryption keys for their personal health data, independent of cloud services, which enables patients and health care providers to securely share sensitive medical data. Similar work was proposed by C.-L. Chen et al (65), who utilized the features of mobile devices to support secure medical data exchange in a cloud environment.…”
Section: Technologymentioning
confidence: 99%